Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/s1881-8366(13)80009-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Indicator for Greenhouse Air Circulator Performances

Abstract: Although air circulators are commonly used in agricultural buildings, it is difficult to evaluate the practical performance of many such air circulators currently available in Japan. This study compares the air circulation performances of six commercial air circulators and demonstrates that the distribution of air velocity generation varied among them. Although the power consumption significantly correlated with the range of air circulation observed, the airflow rate listed in the specifications did not. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The first is the uneven distribution of CO 2 in the cultivation area. Using circulation fans to provide air movement seems to be an ideal method for solving this problem 45 . However, in this study, the cultivators did not use circulation fans in the greenhouses, possibly due to anticipated pest control difficulties.…”
Section: Eco-friendly Strategy For Co 2 Enrichment In Commercial Gree...mentioning
confidence: 99%
“…The first is the uneven distribution of CO 2 in the cultivation area. Using circulation fans to provide air movement seems to be an ideal method for solving this problem 45 . However, in this study, the cultivators did not use circulation fans in the greenhouses, possibly due to anticipated pest control difficulties.…”
Section: Eco-friendly Strategy For Co 2 Enrichment In Commercial Gree...mentioning
confidence: 99%
“…The air circulation coverage of six commercial fans was previously investigated using an identical protocol (Kuroyanagi 2013a). Airflow created by each fan was measured in a closed and empty garage (8.5 m in width, 33.6 m in depth, and 6.1 m in height).…”
Section: Performance Indicatormentioning
confidence: 99%
“…The authors did not discuss the reason why horizontal airflow reduced the vertical gradient of air temperature and relative humidity. It could be explained by a circulation of airflow along the gable end wall of the high tunnel because airflow from a commercial air circulator reaches 20 m and more ahead (Kuroyanagi 2013a). Matsuura et al (2004) also reported that air circulation significantly increased the yield in January from 369 g m -2 for the control tunnel to 622 g m -2 for the tunnel with the fan (P = 0.0047).…”
Section: Uniform Air Temperature and Humiditymentioning
confidence: 99%
“…In a study on the influence of air disturbance on the variation of canopy temperature in a double-span greenhouse, Ishii et al (2012) found that the SD of canopy temperature under air disturbance with air velocity of 0.5 m/s was less than 0.6°C, and the SD of canopy temperature without air disturbance was more than 1.1°C. Stagnant air will form a boundary layer on the surface of plants, and as a result, the physiological processes of crops are suppressed (Kuroyanagi, 2013;Kuroyanagi et al, 2013;Takayama et al, 2014). Appropriate air disturbance can regulate the microenvironment of plant canopy leaves, promote energy exchange between the crop canopy and the surrounding environment, reduce CO 2 exchange resistance, increase CO 2 concentration in the microenvironment of leaves, and improve the transpiration rate and promote photosynthesis (Elings et al, 2007).…”
mentioning
confidence: 99%